Effect of Liquidity and Managerial Ownership on the Usage of Derivative Instruments and Company Risk - Rahyuda, Henny; Candradewi, Made Reina (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan, 2022)
This study aims to analyze the effect of liquidity, managerial ownership and use of derivatives on corporate risk in the Indonesian capital market, specifically manufacturing companies listed on the IDX.. This research was conducted using a quantitative approach. The population in this study are all manufacturing companies listed on the IDX. The sampling technique used was purposive sampling method. The companies included in the sample of this study are manufacturing companies that use derivative instruments and are always listed on the IDX from 2016 to 2018. A total of 12 companies can be used as final samples in this study. Based on the results of regression analysis and mediation test, it can be concluded that the managerial ownership variable has a significant positive effect on the Usage of Derivative Instruments. The variable Usage of Derivative Instruments has a significant negative effect on company risk. The Usage of Derivative Instruments is able to mediate the relationship between managerial ownership and corporate risk